Contributions to the theory of diffusion in gases and liquids - Yang, Li-Ming (The University of Edinburgh, 1948)
The theory of diffusion in gases has been approached in two different ways in the past. The first is by means of the old free path theory initiated by Maxwell [and] Boltzmann, improved by Tait, Meyer, Jeans and others which though unable to give exact quantitative results owing to the assumption that molecules after collision are distributed in the Maxwellian type in non-uniform gases, provides a simple vivid picture of the complex molecular transport phenomena in gases. The second one due to Chapman and Enskog is to find the deviation from the Maxwellian velocity distribution in a non-uniform gas by solving Maxwell and Boltzmann's Collision equation.
Keywords: Diffusion; Gases; Liquids; Collisions